2013
DOI: 10.1038/nmeth.2360
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic protein clustering and signaling activation in mammalian cells

Abstract: We report an optogenetic method based on Arabidopsis thaliana cryptochrome 2 for rapid and reversible protein oligomerization in response to blue light. We demonstrated its utility by photoactivating the β-catenin pathway, achieving a transcriptional response higher than that obtained with the natural ligand Wnt3a. We also demonstrated the modularity of this approach by photoactivating RhoA with high spatiotemporal resolution, thereby suggesting a previously unknown mode of activation for this Rho GTPase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
453
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(492 citation statements)
references
References 23 publications
23
453
0
3
Order By: Relevance
“…2) without the need for exogenous cofactors, thus PHR meets the requirements for an ideal optogenetic dimerizer. The lightdependent homo-interaction property of PHR described here has been recently reported, showing that PHR can be oligomerized and form clusters by blue-light illumination in mammalian cells 31 . Thus, as suggested 31 , our results further support that PHR can be harnessed as a single light-sensitive module to induce protein-protein interaction and can be adapted to a broad range of signalling molecules, including other RTK families.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…2) without the need for exogenous cofactors, thus PHR meets the requirements for an ideal optogenetic dimerizer. The lightdependent homo-interaction property of PHR described here has been recently reported, showing that PHR can be oligomerized and form clusters by blue-light illumination in mammalian cells 31 . Thus, as suggested 31 , our results further support that PHR can be harnessed as a single light-sensitive module to induce protein-protein interaction and can be adapted to a broad range of signalling molecules, including other RTK families.…”
Section: Discussionsupporting
confidence: 68%
“…The lightdependent homo-interaction property of PHR described here has been recently reported, showing that PHR can be oligomerized and form clusters by blue-light illumination in mammalian cells 31 . Thus, as suggested 31 , our results further support that PHR can be harnessed as a single light-sensitive module to induce protein-protein interaction and can be adapted to a broad range of signalling molecules, including other RTK families. Our light-dependent strategy offers several advantages over conventional ligand-based or pharmacological approaches, including those use organic compounds (such as CIDs) and engineered receptors [9][10][11] , for the control of receptor signalling.…”
Section: Discussionsupporting
confidence: 68%
“…9f) (Kennedy et al 2010;Liu et al 2012). Moreover, this approach was used for blue-light-induced protein translocation (Kennedy et al 2010) and for rapid and reversible protein oligomerization in living cells (Bugaj et al 2013). Most recently, Zhang et al developed a new set of tools for light-inducible transcriptional effectors (LITEs).…”
Section: Application Of Light-sensitive Modules In Synthetic Biology mentioning
confidence: 99%
“…The mechanism of light-activation is not fully understood and it has recently been shown that Cry2 oligomerizes into large clusters under blue light in addition to associating with CIB1. This could be a drawback for applications that require precise stoichiometry, but the oligomerization itself has been used for control of protein activation (6). Another dimerization pair is phytochrome B (PhyB) and PIF, also from A. thaliana.…”
mentioning
confidence: 99%